Diversification of the Public Reader in Bogotá (1910- 1924). An Analysis of El Gráfico and Cromos Illustrated Magazines (2016)
El Gráfico (1910-1941) and Cromos (1916-present day) were two widely recognized Colombian magazines of the first decades of the XX c. The objective of both of these publications was the (real and imaginary) configuration of a wide reading public that would consolidate the editorial industry; a possible reason for the inclusion of literature as a comercial Enterprise in these publications. This study will examine the configuration of the reader, as part of the editorial project of both magazines, and the reading (and consumer) practices evident in aspects such as advertising and the writing forms included, such as chronicles, short stories and literary criticism.